Costs of routine immunization services in Moldova: Findings of a facility-based costing study. (7th May 2015) - Goguadze, K.; Chikovani, I.; Gaberi, C.; Maceira, D.; Uchaneishvili, M.; Chkhaidze, N.; Gotsadze, G.
Highlights: The cost of a fully immunizing a child is higher than previous estimates. Good understanding of the major cost drivers is helpful for managing EPI costs. Knowledge of costs helps achieve adequate coverage in a sustainable manner. Abstract: Objective: Available estimates on how much it costs to provide routine immunization services are out-dated. This study attempts to address gaps in evidence by evaluating the total economic and unit costs of delivering routine immunization (RI) services in Moldova as part of a multi-country study on the costs and financing of routine immunization (EPIC). Methods: This cross-sectional study is based on a multistage stratified random sample of fifty primary health care facilities. Data on inputs, prices, and outputs were collected retrospectively for 2011 and analyzed using an ingredient-based costing approach in Excel and SPSS ® . Results: The average total annual facility cost for RI was $11, 943 ranging from $565 to $112, 548 and labor cost was the main driver of routine immunization costs contributing 65%, followed by capital costs – 16.3% and the cost of vaccines and injection supplies accounting for 9%. The average cost per dose was $18.3, the cost per child was $316.6 and the cost per fully immunized child was $332.3. The results show considerable variation in the costs of routine immunization services across facility type and depending on a facility scale i.e. annual doses administered. Conclusions: The study shows that the cost of fully immunizing a child in a middle-income country is much higher than previous estimates. These results will be used by the government for better planning and financing of routine immunization services, leading to greater sustainability.